Accelerated biodegradation and improved mechanical performance of pure iron through surface grain refinement. (15th October 2019) - Bagherifard, Sara; Molla, Mauro Filippo; Kajanek, Daniel; Donnini, Riccardo; Hadzima, Branislav; Guagliano, Mario
Graphical abstract: Abstract: Pure iron and its biocompatible and biodegradable alloys have a high potential to be used for temporary load bearing medical implants. Nevertheless, the formation of passive iron oxide and hydroxide layers, which lead to a considerably low degradation rate at the physiological environment, has highly restricted their application. Herein we used numerical and experimental methods to evaluate the effect of severe shot peening, as a scalable mechanical surface treatment, on adjusting the performance of pure iron for biomedical applications. The developed numerical model was used to identify the range of peening parameters that would promote grain refinement on the pure iron surface. Experimental tests were then performed to analyze the gradient structure and the characteristics of the interface free surface layer created on peened samples. The results indicated that severe shot peening could notably increase the surface roughness and wettability, induce remarkable surface deformation and grain refinement, enhance surface hardness and generate high in-depth compressive residual stresses. The increased surface roughness besides the high concentration of micro cracks and dislocation density in the grain refined top layer promoted pure iron's degradation in the biologically simulated environment. Statement of Significance: Biodegradable metallic materials with resorbable degradation products have a high potential to be used for temporary implants such as screws, pins, staples, etc. They can eliminate the need for implant retrieval surgery after the damaged tissue is healed, and result in reduced patient suffering besides lowered hospitalization costs. Pure iron is biodegradable and is an essential nutrient in human body; however, its application as biomedical implant is highly restricted by its slow degradation rate in physiological environment. We applied a scalable surface treatment able to induce grain refinement and increase surface roughness. This treatment enhances mechanical performance of pure iron and accelerates its degradation rate, paving the way for its broader applications for biomedical implants.